How China Sees the Indo-Pacific : What Next After AOIP? - Ho, Benjamin Tze Ern (2020)
Following the publication of the ASEAN Outlook on the Indo-Pacific (AOIP) earlier this year, Chinese observers have trained their focus on what the AOIP means for Beijing’s relations with Southeast Asia. Come 2020, it is likely that China would demand greater clarity concerning the practical “deliverables” of the AOIP.